OPTIMIZATION OF THE ISI PIRINGKU METHOD IN IMPROVING THE NUTRITIONAL STATUS OF ANEMIA PREGNANT WOMEN IN KARANGPLOSO HEALTH CENTER AREA, MALANG REGENCY - Tutrayani Wijayanti; Reny Retnaningsih; Rani Safitri (Universitas Airlangga, 2023)
Anemia in pregnancy is a problem in Indonesia which is still the focus of attention in treating health problems. The role of cadres as the leading pillar in community services, especially pregnant women, is the main focus that needs to be prioritized. Increasing the knowledge and skills of cadres is important to improve the quality of services to the community, especially anemic pregnant women. By increasing understanding and developing the Isi Piringku approach, this community service seeks to strengthen the position of posyandu cadres to improve the nutritional status of anemic pregnant women. This activity consists of TOT (training of trainers) for cadres. Training activities for cadres consist of material about anemia in pregnant women and efforts to overcome it, as well as training on the Fill My Plate method to improve the nutritional status of anemic pregnant women. This community service activity was carried out in the Karangploso District work area with a focus on selected posyandu targeting anemic pregnant women. The results of this community service activity can be seen by the significant difference between before and after counseling with a p-value of 0.006 (α<0.05) regarding the nutritional status of anemic pregnant women. This community service activity concludes that the counseling and training provided can increase the knowledge of posyandu cadres in improving the nutritional status of anemic pregnant women using the ISI PIRINGKU method as an effort to reduce maternal mortality.